Estado del arte de los modelos de gestión del talento humano y algunos casos de Colombia en el periodo de 2000 a 2015 (2018)
Objective: Identify the state of the art of human talent management models in Colombia in the period from 2000 to 2015. In this article, we could highlight cases of companies in Colombia that have understood the importance of human talent management making efforts to implement a management model that allows them to respond to these new challenges, after making a broad tour of the conceptual elements of this topic. This ends up analyzing the cases of Plesco Industry, the National Police and Ecopetrol, comparing their management with other companies in the sector, each case shows us that, although every day the benefits are greater, some indicators of the systems will continue to identify personnel not satisfied. The results are consistent with the world literature, so Human Resource Management becomes a crucial aspect, because the success and competitiveness of organizations depends largely on what people do and how they do it, then invest in people can generate great benefits, therefore, regardless of the size of the organizations we can guarantee a human resource satisfied and competent. Conclusions: the human talent management models applied in Colombia are in accordance with the state of art and define clear guidelines for the strategic success of the organization